ANALISIS GOOD CORPORATE GOVERNANCE PADA BANK SYARIAH; Analisis Independensi Dewan Komisaris pada Bank Syariah di Indonesia - Atika Lusi Tania (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2017)
The principles of Good Corporate Governance (GCG) is important in Islamic banking. Agency problems in Islamic financial institutions are unique from other financial institutions. The different types of operations and contracts in Islamic banks resulted in widening the separation and control issue that is located under the theory of Agency. Managers at bank syariah not only maximize the shareholder made but also have an obligation to work under Islamic rules and regulations. The other issue is about ownership of shares and double post of Commissioner on the company itself or at other companies. It violates the principles of GCG that is the independence of the Board of Commissioners. The Board of Commissioners in some Islamic banks in Indonesia allegedly still has a stake and a duplicate position. Therefore, based on those explanations, it is quite important to conduct this study on the implementation of GCG in Islamic banking in Indonesia. This samples of this study are all Syariah Bank in Indonesia which have been listed in the Indonesia stock exchange, numbered 11 Islamic banks. This study aims to analyze the corporate governance in Islamic banking in Indonesia especially on the independence of the Board of Commissioners. The benefit of this research is to investigate the practices of corporate governance especially the independence of the Board of Commissioners in terms of share ownership and concurrent positions on Islamic banks in Indonesia. Moreover, based on the data analysis, it was found that the Board of Commissioners on ten syariah banks in Indonesia has a stake in the company or other companies and/or have a concurrent positions at another company, the Board of Commissioners on one Islamic bank has no shares in the company or other companies and/or have a concurrent positions on other companies, and one Islamic bank has a stake in the company or other companies and possess a concurrent positions on other companies. In conclusion, this proves that the majority of the Board of Commissioners on Syariah Bank in Indonesia has not been independent.